Kauṭilya on Legal and Illegal Cancellations of Contracts - Wiese, Harald (Indo-Iranian journal, 2017)
This article tries to clarify Arthaśāstra III.15.1–10 which is a difficult section on legal cancellations of contracts (anuśaya) for merchandise and on illegal ones. Previous translators apparently misunderstood the case of perishable goods and the expression anuśayaṃ dadāti. The view put forward in the present paper builds on the distinction between “Kauṭilya Recension” and “Śāstric Redaction”. However, the sections concerned may contain even more interpolations than previously thought. A related passage on immovable property (AŚ III.9.6–9), specifying fines for unlawful cancellations, is discussed as well.